Merger and Acquisitions Integration, Implementation as Innovative Approach Toward Sustainable Competitive Advantage: A Case Analysis From Chinese Sports Brands - Chiu, Wen-Hong; Shih, Yuan-Shen; Chu, Li-Sheng; Chen, Shieh-Liang (Frontiers in Psychology, 2022)
Brand M&A has long been an extremely common strategy for expanding the scale of an organization and entering new business areas, but various signs show that many brand mergers and acquisitions (M&As) do not add value. They often lose money and fail. This research explores the value, scarcity, and non-replicability of resources in corporate M&A, as well as organizational resource management, innovation resource management, and implementation of the combination of resource utilization and brand strategy that incorporate M&As. Taking 03 of China’s sporting shoe industry cases, this study uses the literature to collect, analyze, and organize the conversations of high-level managers to compare and integrate the motivations of corporate M&As to conduct confirmatory analysis. Using case studies and cross-border M&A related secondary data from 2014 to 2021 and supplemented by senior executives’ conversations, 1,836 articles were collected as analysis units. The research results show that Chinese companies’ cross-border M&A’s main corporate strategic motives have four key elements: accelerated expansion, integration of resources, brand integration, rapid entry into the international market, and obstacles to the construction of new entrants. The research results also show that integrating resources and brand execution strategies after M&As correlates to their success or failure. The purpose of the research was first to discuss brand M&As and corporate strategies in the Taiwanese context. Secondly, it discusses the issue of the use of resources by the acquired party in specific to emerging trends in consumer resistance to innovation and acceptance of technological innovativeness in the sports industry brands. Third, it analyzes the effectiveness of brand strategy integration and implementation. Finally, it provides a strategic reference for brand M&As in the industry.